A correlation of densities of liquid polar and nonpolar refrigerants from critical temperature. (3rd September 2019) - Mousazadeh, M. H.
ABSTRACT: We developed an equation of state based on statistical–mechanical perturbation theory for polar and nonpolar refrigerants. The equation is that the Ihm, Song and Mason, in which the three temperature dependant parameters are, calculated by means of the corresponding states correlations. In this work, it is shown that using the critical constants of fluids as scale constants would correlate the temperature-dependent parameters of the equation of state with sufficient accuracy. We have tested the predicted equation of state against the experimental data for a large number of haloalkanes including a number of the environmentally acceptable HFCs (R23, R32, R41, R125, R134a, R143a, R152a, R227ea, R236ea, R236fa, R245ca, R245fa), the HCFCs (R22, R123, R124, R141b, R142b), the traditional CFCs (R11, R12, R13, R113, R114, R115) and the fluorocarbons refrigerants (R14, R116, R218, RC318). A comparison is also made by other scale parameters based on experimental data.